Christianity under Islam in Jerusalem : The Question of the Holy Sites in Early Ottoman Times - Peri, Oded (Brill Book Archive Part 1, ISBN: 9789004472495., 2001)
A major issue in nineteenth-century world politics, the question of Christianity's holiest shrines in Jerusalem is covered by a large body of literature. Most of this scholarship, however, concentrates on the period when the question of the Holy Sites has already evolved from a domestic Ottoman problem into an all-European issue. Much less is known about this problem in earlier times, when the Ottoman Empire was still a dominant power able to propose solutions free of foreign interference and outside pressures. Based on official Ottoman records found in the registers of the kadi's court in Jerusalem as well as the Prime Ministry's Archives in Istanbul, the present study offers a thorough treatment of Ottoman policy with respect to the Holy Sites during the first two centuries of Ottoman rule in Jerusalem. It focuses on three principal issues: (a) The legal status of the Holy Sites under Ottoman rule; (b) The Ottoman state and the inter-church struggle over the Holy Sites; (c) The Holy Sites as a source of income to the Ottoman state. The discussion of these issues sheds new light on one of the most obscure and controversial chapters in the history of Christianity under Islam in Jerusalem.